The Risks Associated With Percutaneous Native Kidney Biopsies (NKBs) in a Tertiary Care Hospital - Khan, Ikram Zeb; Islam, Farrukh; Ijaz, Samavia; Farooq, Misbah; Altaf, Ashfaq; Khan, Yasser (Biological and Clinical Sciences Research Journal, 2025)
Percutaneous native kidney biopsy (NKB) remains a cornerstone for the histopathological diagnosis of renal diseases. While it is generally considered a safe and effective procedure, the risk of complications—particularly bleeding—necessitates a careful evaluation of its safety profile in local healthcare settings. Objective: To assess the frequency and types of complications associated with percutaneous native kidney biopsies performed under real-time ultrasound guidance in a tertiary care center. Methods: This prospective observational study was conducted at a tertiary care hospital from September 2024 to March 2025. A total of 209 patients scheduled for percutaneous NKB were enrolled using non-probability consecutive sampling. Biopsies were performed under real-time ultrasound guidance using automated biopsy devices. Patients were monitored for complications up to 24 hours post-procedure. Complications were categorized as major (e.g., requirement for blood transfusion, angioembolization, prolonged hospitalization >24 hours, surgical intervention, or procedure-related death) or minor (e.g., self-limiting hematuria or small hematomas). Data were analyzed using SPSS Version 25, with descriptive statistics reported as frequencies and percentages. Results: The mean age of participants was 43.2 ± 16.5 years, and 119 (56.9%) were male. Minor complications were noted in 15 patients (7.1%), including small hematomas in 8 (3.8%) and transient hematuria in 7 (3.3%). Major complications occurred in 12 patients (5.7%). Of these, 5 (2.4%) required blood transfusion, 2 (0.9%) developed major hematomas, 2 (0.9%) experienced prolonged hospitalization, and 1 (0.5%) each required repeat biopsy or intervention due to inadequate specimens. No deaths were reported. Conclusion: Percutaneous NKB is a reliable and generally safe diagnostic procedure for renal pathology. Although minor complications such as transient bleeding are relatively common, serious adverse events remain infrequent. Continued adherence to real-time imaging and post-procedural monitoring protocols is recommended to further minimize risk.